2019
DOI: 10.1007/s12369-019-00565-4
|View full text |Cite
|
Sign up to set email alerts
|

It’s in the Eyes: The Engaging Role of Eye Contact in HRI

Abstract: This paper reports a study where we examined how a humanoid robot was evaluated by users, dependent on established eye contact. In two experiments, we manipulated how the robot gazes, namely either by looking at the subjects' eyes (mutual gaze) or to a socially neutral position (neutral). Across the two experiments, we altered the level of predictiveness of the robot's gaze direction with respect to a subsequent target stimulus (in Exp.1 the direction was non-predictive, in Exp. 2 the gaze direction was counte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 60 publications
(52 reference statements)
6
37
0
Order By: Relevance
“…In line with the previous works, manual response times showed a reliable gaze cuing response only after eye contact episodes. The rationale behind the studies discussed above is that the enhanced gaze cueing effect after eye contact may have evolved to facilitate interpersonal communication and social coordination (see also 6,30 ). Indeed, receiving eye contact from other individuals could indicate their intention to interact with us.…”
mentioning
confidence: 99%
“…In line with the previous works, manual response times showed a reliable gaze cuing response only after eye contact episodes. The rationale behind the studies discussed above is that the enhanced gaze cueing effect after eye contact may have evolved to facilitate interpersonal communication and social coordination (see also 6,30 ). Indeed, receiving eye contact from other individuals could indicate their intention to interact with us.…”
mentioning
confidence: 99%
“…In addition, eye gaze and eyebrow would also contribute to the people’s credibility. Because eye gaze and related eyebrow are crucial attention-catching cues for social recognition and social interest, the majority research on human facial features suggested that a direct-gaze (vs. looking at others) face with thin (vs. thick) and up-shaped (vs. down) inner ridge eyebrows was anticipated to be not only more trustworthy but also more attractive [ 52 , 57 , 59 , 64 , 67 , 71 , 77 ]. In the field of a social robot, there might exist a nuanced relationship between gaze and trustworthiness: Stanton and Stevens [ 66 ] suggested constant gaze, compared with averted gaze, might indicate dominance, rather than trustworthiness, and this effect was especially significant when female participants tried to evaluate the robot.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have suggested facial trustworthiness communication mainly depends on the interaction among static features, dynamic expressions, and general appearance characteristics [ 41 ]. As for static features, eye and face shape might be the most promising area because eye is a salient facial feature for catching people’s attention [ 52 , 57 , 59 , 64 , 67 , 71 , 77 ] while face shape (e.g., fWHR and forehead) is the most prominent human secondary sexual characteristics [ 25 ] and also the most obvious feature when evaluating a face [ 90 ]. Regarding dynamic facial features, the mouth region is the most pronounced feature for emotional expressions (happiness, anger, or sadness) due to its spontaneous muscle activity around mouth and lips [ 91 ].…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Additionally, despite the limitations regarding the implementation of biologically inspired robot eyes both in terms of cost and complexity, mechanical human-like eyes that can enable a gaze-cueing procedure are recommendable (for a review, see Admoni & Scassellati, 2017). It would also be beneficial if robots are endowed with algorithms that allow for the establishment of eye contact with participants since it has been shown that eye contact initiated by a humanoid robot increases perceived human-likeness and engagement with the robot (Kompatsiari, Ciardo, Tikhanoff, Metta, & Wykowska, 2019b). It also enhanced joint attention .…”
Section: General Guidelines For Using Embodied Robots In Joint Attentmentioning
confidence: 99%